PENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) BERORIENTASI KECAKAPAN HIDUP (LIFE SKILL) PADA MATERI SISTEM REPRODUKSI MANUSIA - AMELIA PUTRI, VINDA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
Learning based on life skills need to be taught to students in order to form an independent and creative person. The purpose of this study are 1) generates life skills worksheets in the reproductive system material viable in terms of content, language and appearance, 2) describe the rational skills and social skills of students, 3) improve student learning outcomes by using design